Galeria handlowa jako przestrzeń edukacji nieformalnej - Rudnicka, Maria (Studia Edukacyjne, 2019)
The goal of the study is to answer the question about the educational values of cultural promotional events held in shopping malls. To achieve this goal, an ethnographic research was performed during three events in two shopping malls in Wrocław. It consisted of participatory observation and interviews with 6 participants of the events. The research is based on Knud Illeris’s theory of learning through everyday life (non-formal learning). During the study, it was observed that the organizers of the events use the newest methods of learning (including new technologies). The information is transferred in various ways and the extra attractions that are part of the events engage participants in creative activities. The gained knowledge can be theoretical or practical and it can encourage participants to change their life habits or to undertake various activities in their lives. It also makes accessible the previously inaccessible areas of reality. New knowledge usually does not create new structures and basically reconstructs the existing ones (accommodation learning). The learning process in shopping malls during the cultural events is a byproduct or a side effect of promotional activities, yet it takes place and it can improve the quality of life of the participants. Thus, a shopping mall, an institution of the consumer society, becomes an institution of the society of knowledge.